Spatial patterns of smrs due to the virus A(H1N1)pdm09 during the pandemic in Greece in 2009 – 2010 - Leonidas DOUKISSAS; Stamatis KALOGIROU; Cleon TSIMBOS (European Journal of Geography)
This paper aims to study the spatial structure of deaths due to the A(H1N1)pdm09 swine virus in Greece in order to identify vulnerable and resilient regions. The study period refers to the school year 2009-2010 when a swine flu pandemic took place affecting large numbers of the population including students. The deaths due to the A(H1N1)pdm09 virus have been recorded in Greece by the Hellenic Centre for Disease Control and Prevention (HCDCP). Based on these deaths and the 2011 Census for Population statistics, we calculated the Standardized Mortality Ratios (SMRs) as well as the A(H1N1)pdm09 age-specific death rates. The statistical significance of SMRs was evaluated using a chi-square test, while Empirical Bayesian procedures were employed to smooth the observed standardized mortality ratios. The geography of the analysis refers to the 13 administrative regions in Greece (EU NUTS II). The results are interesting, and the spatial patterns suggest significant inequalities in the SMRs across these regions. At the same time, we discuss the possible failure of the vaccine coverage, especially in regions where our study revealed most affected, in order to help policymakers to be better prepares for a future epidemic.